Utilizing Educational Technologies to Optimize Student and Teacher Learning at Dharma Laksana Mataram Orphanage - Paula Dewanti; Ni Nyoman Supuwiningsih; Desak Putu Saridewi (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2021)
Educational technology is the study and practice of using technology to facilitate and enhance learning performance. During the Covid-19 pandemic, digital learning and the use of information technology were one of the solutions to minimize the risk of Covid-19, according to the government's health protocol. As a Non-Governmental Organization (NGO), the Dharma Laksana Orphanage receives computer set donations from their funders. Based on preliminary reviews, the use of these computer devices is not optimal, both for students and teachers. The inability to optimize the use of computer devices seems to have an impact on the effectiveness of learning approaches by utilizing information technology. This Community Service was performed using the Service Learning methodology and was designed to assist in the development of human resources related to learning methods and media used during the Covid-19 pandemic. During this activity, Edmodo, the leading social learning platform, was successfully introduced. Blended Learning with Google Apps is also covered. It increased both student and teacher awareness of digital learning, as well as teacher competence in creating interactive learning media, by introducing a variety of educational platforms.